Game-based learning approach for learning - Tan, Huei Lie (2019)
Game-based learning indicates the idea of using video games as education tools. The main purpose of this project is to deliver a game on mobile platform with the idea of game-based learning concept. Several problems and flaws from existing education system and game are analyzed in order to overcome them in this project. For example, traditional teaching method consists of shortcoming which requires much effort from the teacher to deliver the knowledge to the students by using instructions and guidance. At the same time, students have to stay focus in order to remember those instructions from teacher. Furthermore, the existing education games have repetition contents and limited choice of difficulty option. The player may lose their motivation if the game is too easy and get bored or too hard and get frustrating after trying the game. If either situations happen, it is just a matter of time for the player to give up the game eventually. These issues will be taken into consideration during the development of the game as some important features of the game. Android Studio with the involvement of LibGDX will be used as the programming tools to build the game. Eventually, the game developed will be playable on mobile device with Android platform. Lastly, in order to validate the functional and non-functional requirements of this project, black box testing will be conducted on the application to ensure minimum amount of defects in the system. This project has proposed in hope of the games can offer an enjoyable and unforgettable experience and most importantly, granting the possibility for the advancement of learning.